URGENSI PENERAPAN HUKUM TATA NEGARA DARURAT DALAM PENANGGULANGAN BENCANA CORONA VIRUS DISEASE 2019 DI INDONESIA - Konang Perdana Putra; Gusliana HB; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The development of the spread of this virus continues and occurs not only in Chinabut spreads widely throughout the world, including one of them to Indonesia. With a largenumber of deaths and endangering the country, on January 30 2020 the World HealthOrganization (WHO) declared the Corona Virus Disease 2019 outbreak or what is knownas Covid-19 as a public health emergency that is worrying the world and on March 11 2020an outbreak was announced. as a pandemic. So that various protection efforts are carriedout by each country with different policy implementations. Because compared to otheraspects, health is one of the basic human needs and without human life becomesmeaningless. Even though there have been regulations governing health under Law Number36 of 2009 concerning health, arrangements to tackle the spread of Covid-19 in Indonesiaare not only sufficient based on the health law alone, it requires policies from thegovernment to tackle Covid-19 by based on state ideology as well as internationalconventions.Regarding the Covid-19 pandemic from the perspective of this ConstitutionalEmergency Law, and looking at the policies and legal instruments that have been stipulatedby the President, it does not categorize Covid-19 into a dangerous category but falls into thesecond terminology, namely urgent urgency in accordance with Article 22 of theConstitution. 1945 Indonesia is currently in a state of emergency as stated in PresidentialDecree (Keppres) Number 11 of 2020. These difficult conditions require appropriatepolicies in accordance with more advanced and responsive efforts in accordance with lawsand regulations. provision.The Urgency of Implementing Emergency Administrative Law in Managing theCovid-19 Disaster can be an instrument for the government in overcoming an abnormalstate of affairs. Therefore, this Emergency Constitutional Law can be an effective andefficient alternative or solution in overcoming a state problem that is currently in anemergency. In the conditions of the Covid-19 pandemic, the government made a legalchoice as a Health Emergency, but in overcoming the Covid-19 pandemic, various legalinstruments have regulated it so that the government declared the Covid-19 pandemic anational disaster with Presidential Decree (Keppres) No. 11 of 2020 .Keywords: Corona Virus Disease, Lockdown, Constitutional Law Emergency.